2012
DOI: 10.1080/10508422.2011.641832
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Contributing to Wrongdoing in Medicine: A Criterion-Based Review of Studies and Cases

Abstract: In this paper we describe our approach to understanding wrongdoing in medical research and practice, which involves the statistical analysis of coded data from a large set of published cases. We focus on understanding the environmental factors that predict the kind and the severity of wrongdoing in medicine. Through review of empirical and theoretical literature, consultation with experts, the application of criminological theory, and ongoing analysis of our first 60 cases, we hypothesize that 10 contextual fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 94 publications
(111 reference statements)
0
23
0
Order By: Relevance
“…An Environmental Factors Score Sheet was developed based upon (1) an extensive review of the psychological and social science literature on factors that correlate with or predict professional wrongdoing (DuBois et al 2012) and (2) qualitative analysis of the first 30 cases by the research team to identify any additional environmental variables that might predict the wrongdoing. It was modeled upon “benchmark” scoring guides used in other historiometric studies (O’Connor et al 1995).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An Environmental Factors Score Sheet was developed based upon (1) an extensive review of the psychological and social science literature on factors that correlate with or predict professional wrongdoing (DuBois et al 2012) and (2) qualitative analysis of the first 30 cases by the research team to identify any additional environmental variables that might predict the wrongdoing. It was modeled upon “benchmark” scoring guides used in other historiometric studies (O’Connor et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Wrongdoing among researchers harms participants (DuBois 2008), pollutes the scientific literature (Titus, Wells, and Rhoades 2008), and damages public trust (Coughlin, Barker, and Dawson 2012). While many articles have been published on professional wrongdoing, our literature review found no studies that examined the rich contextual details of large sets of historical cases of wrongdoing (DuBois et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it did not systematically examine environmental factors that might be correlated with IPCS. A review article by DuBois and colleagues identified 10 environmental factors that may be correlated with professional wrongdoing in medicine (DuBois, et al, 2012). By reviewing empirical studies and actual cases, a series of environmental factors were identified that may contribute to wrongdoing by providing motive, means, or opportunity—three elements common to general forensic theory (Jones, 2010; Maguire, Reiner, & Morgan, 2007).…”
mentioning
confidence: 99%